Violence and LGBTQIA+ Population: Impact on Mental Health and the importance of the Care Network (Research, Society and Development, 2022)
This study aims to understand the relationship between violence against the LGBTQIA+ population and the impact on mental health, presenting a network of attention and care. It will be presented as the main identified violence, the impact on mental health of reference and the main services that refer to this network. It is a bibliographic study, of a qualitative nature, consisting of a bibliographic review, with searches in the main bibliographic and reference sites. They were delimited as searches in the categories of texts published in the last five years, from 2017 to 2022, with the inclusion keywords: violence; LGBTQIA+; mental health; attention network. One can understand the importance of working with violence, its ramifications and its results, being able to understand an integrated vision in the cultural context as its results, being an integrated vision of the cultural results as its biophobia and possible to understand how LGBT people are a sociocultural problem.